FV 13 Transcranial direct current stimulation modulates stroke-induced secondary thalamic neurodegeneration in mice. (May 2022) - Blaschke, S.J.; Vlachakis, S.; Olschewski, D.N.; Ladwig, A.; Anna-Lena, C.; Backes, H.; Aswendt, M.; Fink, G.R.; Schroeter, M.; Rueger, M.A.
Abstract : Introduction: Transcranial direct current stimulation (tDCS) non-invasively promotes recovery after stroke ( Braun et al. Exp. Neurol. 2016; Hummel et al. Brain 2005 ). Stroke affects entire networks beyond the focal lesion, impacting post-stroke impairment ( Blaschke et al. Stroke 2021 ). The thalamus constitutes a central hub due to its numerous functional connections but is also prone to secondary injury ( Cao et al. Front. Neurol. 2020 ). Under the hypothesis that tDCS promotes recovery by supporting neuroprotection, we investigated the effects of tDCS on secondary thalamic neurodegeneration after stroke. Methods: Cortical stroke was induced in the sensory-motor cortex (photothrombosis model in mice). Starting three days after stroke, cathodal tDCS over the ipsilesional somatosensory cortex was performed daily for ten days (39.6 kC/m 2 ), sham-stimulated mice served as control. Behavioral tests over time assessed functional recovery. Secondary degeneration of the ipsilesional thalamus was evaluated ex vivo 28 days after stroke. Using an atlas-based registration pipeline ( Pallast et al. J. Neurosc. Methods 2019 ), the absolute number of GFAP+ astrocytes and relative number of ipsilesional NeuN+ neurons compared to the contralateral unaffected thalamus were evaluated. Lesion maps based on T2-weighted Magnetic Resonance Imaging (MRI) before tDCS were used for voxel-based lesion-symptom mapping (VBLSM) to evaluate the effect of the lesion location on remote neurodegeneration. Functional connectivity (FC) between the lesioned sensorimotor cortex and the ipsilesional thalamus was measured by resting-state functional MRI. Additionally, glucose metabolism after a likewise tDCS regimen in healthy mice was measured by positron emission tomography compared to sham stimulation. Results: Repetitive tDCS decreased the ipsilateral thalamic glucose metabolism in unlesioned animals, while accelerating motor recovery after stroke. Four weeks after cortical stroke, secondary glial scaring was found in the ipsilesional thalamus, most pronounced in the posterior (Po), ventral posterolateral (VPL), and ventral posteromedial (VPM) nucleus, its extent correlating to the cortical lesion size (R 2 =0.3, p<0.01). Neurodegeneration was associated with a lesion cluster (VSBLM, p<0.05) extending laterally and including the callosal white matter tracts as well as deeper primary somatosensory layers. A decrease in FC between the primary somatosensory area of the lower limb (SS-LL) and the thalamus correlated with secondary neurodegeneration (R 2 =0.25, p<0.01). Intriguingly, in contrast to glial scaring, tDCS reduced thalamic neurodegeneration by over 60% (p<0.05). Conclusion: Cortical stroke induced network changes and led to remote secondary structural impairment of the thalamus, depending on the affection of corticothalamic connections. TDCS mitigated this remote secondary neurodegeneration. Data suggest previously unknown effects of tDCS on remote brain regions after stroke.